2011
DOI: 10.1016/j.febslet.2011.03.039
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 inhibits proliferation of small cell lung cancer cells by targeting SLC7A5

Abstract: Edited by Tamas Dalmay Keywords:Small cell lung cancer miR-126 SLC7A5 G1 delay a b s t r a c t Despite intensive efforts to improve therapies, small cell lung cancer (SCLC) still has a dismal median survival of 18 months. Since miR-126 is under-expressed in the majority of SCLC tumors, we investigated the effect of miR-126 overexpression on the proliferation and cell cycle distribution of H69 cells. Our results demonstrate that miR-126 inhibits proliferation of H69 cells, by delaying the cells in the G1 phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 25 publications
1
85
0
Order By: Relevance
“…Gene expression in cancer is regulated by oncogenes and tumor suppressor genes. In recent years, with the identification of microRNAs (miRNAs) and their functions, Li et al (20) and Miko et al (21) reported that PLK2 was a target gene of miR126. miRNAs are a type of small non-coding RNA, ~22-nucleotides, which downregulate the translation of target mRNAs (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression in cancer is regulated by oncogenes and tumor suppressor genes. In recent years, with the identification of microRNAs (miRNAs) and their functions, Li et al (20) and Miko et al (21) reported that PLK2 was a target gene of miR126. miRNAs are a type of small non-coding RNA, ~22-nucleotides, which downregulate the translation of target mRNAs (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PLK2 seems to inhibit oncogenic transformation (26). A previous study showed that PLK2 is a target gene of miR-126 (21,27), which is also as a tumor suppressor (12). However, the inhibitory effects of a specific miRNA on a target gene appear to be cell type-specific.…”
Section: Mir-126 Inhibits Growth Of Sgc-7901 Cells By Synergisticallymentioning
confidence: 99%
“…To date, the target genes of miR-126 that have been confirmed are PI3KR2 (18), IRS-1 (19), Crk (12), SOX2 (13), ADAM9, MMP7 (20) and SCL7A5 (21). Except for SOX2, which is a tumor suppressor, other genes are involved in tumor formation and progression.…”
Section: Mir-126 Inhibits Growth Of Sgc-7901 Cells By Synergisticallymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that miRNAs regulate many tumor-related processes including proliferation, migration, and invasion [5]. Accumulating studies has revealed that dysregulation of miRNAs occurs in various human malignancies, including GC [6,7]. Among these miRNAs, miR-339 was reported to be deregulated in breast and colorectal cancer [8,9].…”
Section: Introductionmentioning
confidence: 99%